Contextual Arabic Vocabulary Learning Through Meaningful Pedagogical Approach: A Case Study at SD IT Alam Talago, Indonesia - Titi Fitri; Beri Nopriansyah; Nilna Aldzakhiroh; Neli Asmaniah; Azizah Rahmah (Abjadia : International Journal of Education, 2026)
This study describes the implementation of Arabic vocabulary instruction using a meaningful pedagogical approach at SD IT Alam Talago, Indonesia, emphasizing connections to real-life experiences and active student involvement. Using a qualitative descriptive case study method, the research involved one Arabic teacher and 28 fifth-grade students selected through purposive sampling. Data were collected over one month via observation, interviews, and documentation, then analyzed using the Miles and Huberman model (data reduction, presentation, and conclusion drawing), with validity ensured through triangulation and member checking. Findings indicate that lesson plans were designed based on student characteristics, contextual themes, and environmental learning resources. Instruction employed Total Physical Response (TPR), Communicative Language Teaching (CLT), and Inquiry-Based Learning, encouraging active engagement in vocabulary use, enabling most students to understand and use vocabulary in simple contexts. Evaluation was conducted continuously through pre-tests, formative assessments, and post-tests covering comprehension, usage, pronunciation, and engagement. Overall, Arabic vocabulary instruction using this approach demonstrates a more contextual and student-centered learning process, although outcomes still depend on individual student circumstances and characteristics.